DESAIN KARAKTER MASKOT ANIME UNTUK MENINGKATKAN MARKETING VIULA STUDIO - Adelia Aura Diva Zainanda; Hersatoto Listiyono (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
A mascot is a character or symbol used to represent a brand, product or company. Mascots aim to create a strong, easily recognizable identity and give a positive impression. The definition of a mascot is very important in relation to the branding carried out by the company. In this article the author wants to design a work about mascot design based on the background of one of the studios in the Semarang city area, namely Viula Studio. VIULA STUDIO wants to strengthen its identity by showing its identity using its own logo and also wants to have its own mascot.